Circadian rhythm of anti-fungal prenylated chromene in leaves of Piper aduncum - Morandim, A. D.; Bergamo, DCB; Kato, M. J.; Cavalheiro, Alberto José [UNESP]; Bolzani, Vanderlan da Silva [UNESP]; Furlan, Maysa [UNESP] (Wiley-Blackwell, 2005)
Leaves of Piper aduncum accumulate the anti-fungal chromenes methyl 2,2-dimethyl-2H-1-chromene-6-carboxylate (1) and methyl 2,2-dimethyl-8-(3'-methyl-2'-butenyl)-2H-1-chromene-6-carboxylate (2). The enzymatic formation of 2 from dimethylallyl diphosphate and I was investigated using cell-free extracts of the title plant. An HPLC assay for the prenylation reaction was developed and the enzyme activity measured in the protein extracts. The prenyltransferase that catalyses the transfer of the dimethylallyl group to C-2' of 1 was soluble and required dimethylallyl diphosphate as the prenyl donor. In the leaves, the biosynthesis of the prenylated chromene 2 was time-regulated and prenyltransferase activity depended upon circadian variation. Preliminary characterisation and purification experiments on the prenyltransferase from P. aduncum have been performed. Copyright (C) 2005 John Wiley & Sons, Ltd.
Keywords: prenyltransferase; chromenes; circadian rhythm; anti-fungal activity; Piper aduncum; Piperaceae